Penyusunan Laporan Keuangan berbasis Spreadsheet untuk Badan Usaha Milik Nagari (BUMNAG) di Tanah Datar Sumatera Barat - Rita Rahayu; Verni Juita; Husna Roza; Annisa Rahman; Deny Yohana; Rayna Kartika (Penerbit Goodwood, 2022)
Purpose: the purpose of this activity is to assist Village Owned Enterprises (BUMDes) in compiling their financial reports by designing simple programs using MS Excel.. Method: the are 4 stages conducted in this activity, which are identification stage of the business field, designing code of account, designing simple application with MS Excel, and training the users. Result: The result of this activity is a simple application for preparing financial reports using the excel program. This application can help BUMDes managers in preparing their financial reports Contribution: The results of this activity are very useful for BUMDes managers because it can help them in preparing financial reports